"Study and Identification of the Etiological Agents of Onychomycosis in Tehran, Capital of Iran" - M Gerami shoar; K Zomorodian; M Emami; B Tarazoei; F Saadat (Tehran University of Medical Sciences, 2002)
Onychomycosis is the fungal infection of the nails with worldwide occurrence, caused by various species of dermatophytes, yeasts and molds. In addition, of pain and physical effect of onychomycosis that may interfere with individual's personal and professional life, it may also causes negative psychosocial consequences in patients. Concerning increase of onychomycosis during recent decades and effect of different climates, professional and socio-economic conditions in prevalence of onychomycosis, local investigation for defining of incidence and causative agents of onychomycosis seems necessary. In the present study, 252 patients suspected to onychomycosis were examined by direct microscopy and cultural methods. 28.3% of patients were male and the rest were female. Specimens were tested by direct microscopic examination using potassium hydroxide 20% and culturing on Sabouraud's dextrose agar (S) and Sabouraud's containing cyclohexamide and chloramphenicol (Scc mediums). Direct microscopy test were negative in 61.1% nail specimens and positive in rest of them. Among these positive cases, 12.3%(n=31) specimens presented branching mycelium with arthroconodia, and 21%(n=53) specimens presented blastoconidia and pseudohyphe. Beside, saprophytic mycelium has been observed in 5.6 %( n=14) of positive cases. The isolated causative agents from culture of specimens according to their frequencies were as follows: Candida albicans (13.7%), Trichophyton mentagrophytis (8.3%), Candida species (6.9%), Aspergillus flavus (2.9%), Aspergillus niger (1.5%), Scopolariopsis (1%), Trichophyton rubrum (1%) and Fusarium (0.5%). The majority of the patients were women and in both sexes, the most cases of infections were observed in the individuals who were 60-70 year old. The rate of effected fingernails and toenails were almost equal. Concerning the results of culture of specimens, Candida was the most prevalent causative agent in the fingernails such as Trichophyton (esp. Trichophyton mentagrophytis) in toenails. The most prevalent none dermatophytic moulds were Aspergillus species in particular in toe nails.